A Finite Element Approach to Conduct Machinability Studies on Age-Hardened AA6061 Matrix Hybrid Composites - Anand Pai; Laxmikant Keni; Chandrakant R Kini (Journal of Engineering and Technological Sciences, 2022)
AA6061, a popular structural material, has found widespread usage in the automotive and aerospace domains. The current work explored the effect of the improvement of mechanical properties on the machinability of AA6061 through finite element analysis. Three compositions of AA6061 containing 2 wt.% graphite and 0, 2, 4 wt.% granite dust were fabricated by stir casting.  In the current work, a finite element model of a slab milling cutter with eight teeth was designed with high-speed steel (HSS) as the tool material. The LS-DYNA module of ANSYS was used for simulation of the milling operation, selecting two peripheral speeds for the cutter during the machining of the workpiece. Surface milling was carried out on the cast slabs of the three compositions to study chip formation. At higher cutting speeds, there was an increase in the von Mises stress as well as material deformation. An increase in the weight fraction of the ceramic fillers led to a corresponding increase in the von Mises stress and material deformation. The experimental results from face milling of the three compositions showed that the surface roughness increased with an increase in the content of ceramic fillers and a decrease in chip size.